Impact of potassium promoter on Cu–Fe based mixed alcohols synthesis catalyst. (15th January 2015) - Ding, Mingyue; Tu, Junling; Qiu, Minghuang; Wang, Tiejun; Ma, Longlong; Li, Yuping
Highlights: Adding K facilitated the immigration of bulky iron species to surface layers. Adding potassium strengthened the interaction of Fe–K on the surface layers. Increasing K content facilitated the formation of C 2 + OH . A maximum in catalytic activity is obtained at 0.5 wt.% of potassium loading. Abstract: Impacts of K promoter on microstructures of a precipitated Cu–Fe based catalyst were studied by N2 -physisorption (BET), X-ray photoelectron spectroscopy (XPS), X-ray diffractometer (XRD) and hydrogen temperature-programmed desorption/reduction (H2 -TPD/TPR). Mixed alcohols synthesis (MAS) was carried out in a fixed-bed reactor. The results indicated that incorporation of K in the Cu–Fe based catalyst decreased the surface area of the particles, whereas promoted the immigration of bulky iron species to surface layers and strengthened the interaction of surface Fe–Cu. The increase of K concentration weakened the H2 chemisorption and restrained the reduction of both the Cu and Fe species. The catalytic activity and mixed alcohols selectivity increased accompanied with a gradually increasing K concentration, and reached the highest values as the amount of K increased to 0.5 wt.%. Subsequently, the MAS activity and selectivity C 2 + OH presented a decreasing trend. In addition, the increase of K concentration facilitated the formation of heavy hydrocarbons.